Thyroid Association Ophthalmopathy in Hashimoto’s Thyroiditis: a Case Report - JAIN, Deepak (Maedica (Bucur), 2017)
Thyroid associated ophthalmopathy is a constellation of symptoms caused by an autoimmune process involving the orbital tissue. It is common in hyperthyroid patients due to Graves’ disease and also reported in euthyroid and hypothyroid Graves’ patients with positive thyroid receptor antibodies. But in Hashimoto’s thyroiditis, thyroid associated ophthalmopathy is a rarely reported and poorly understood entity. Here we report thyroid associated ophthalmopathy in a patient with hypothyroidism and negative thyroid receptor antibodies who showed heterogeneously hypoechoic thyroid gland on ultrasonography, diffuse lymphocytic infiltrate on fine needle aspiration citology and reduced 99m Tc radioisotope uptake, supporting the diagnosis of Hashimoto’s thyroiditis. The patient was treated with levothyroxine and artificial tear drops.